SETTLEMENT HOUSEHOLD LIVELIHOODS FOR POOR FISHERMEN: THE CASE OF CAM RANH RESERVOIR,KHANH HOA PROVINCE - Dao, Ha Thi Thieu; Manh, Pham Hong (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
This study aims to find solutions to solve the basic livelihoods of poor households in the tide reservoir Central Coast. The study results show that livelihoods of majority of families living around Cam Ranh reservoir depend mainly on fisheries resources. The increase effort in fishing effort using different fishing means has caused challenges for local government in solving problems of livelihood, environment and resources. Regression model finds out that besides demographic characteristics: the dependency ratio, education of household members and employment rate of adults, an increase fishing effort (boat) has affected the income and expenditure of poor households. Based on these findings, the authors suggest some recommendations to settle harmonious relationship between livelihoods and the environmentfor the poor fisherman in this area.